2018
DOI: 10.18433/jpps30017
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Modulates the Expression of Renal Drug Transporters in HIV-1 Transgenic Rats

Abstract: PURPUSE: Bacterial co-infections and low grade endotoxemia are common in HIV patients. Inflammation due to endotoxin or HIV may influence the expression and activity of transporters. Kidney transporters influence renal drug clearances including many antiretroviral agents. Our objective was to study the effect of endotoxin and HIV on the renal expression of drug transporters in an HIV-transgenic (HIV-Tg) rat model. These rats develop immune dysfunction and AIDS-associated conditions like humans. METHODS: Endoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Therefore, the implications of decreased transcript levels are not clear. An endotoxin-mediated downregulation in the renal mRNA and protein expression of ENT1 has been previously reported in transgenic-HIV male rats [60]. We previously found that poly I:C imposed an increase rather than a decrease in the renal mRNA expression of Ent1 in pregnant rats at term [16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, the implications of decreased transcript levels are not clear. An endotoxin-mediated downregulation in the renal mRNA and protein expression of ENT1 has been previously reported in transgenic-HIV male rats [60]. We previously found that poly I:C imposed an increase rather than a decrease in the renal mRNA expression of Ent1 in pregnant rats at term [16].…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the implications of these findings are not clear. Endotoxin exposure has also been found to decrease transcript levels of Pept2 in the kidneys of male rats and mice [60].…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Schmidt-Lauber et al reported that the cytokines TNF-α, IL-6, and IL-1β decreased the expression of MATE1 mRNA and protein in MATE1-transfected HEK-293 cells [26]. The mRNA expression of OCT2 and MATE1 was found to be decreased in endotoxin-infected mice, which were characterized by elevated serum levels of IL-6, TNF-α, and IFN-γ [27]. In a rat model of hyperuricemia, the mRNA levels of MATE1 and OCT2 were decreased, leading to an increased accumulation of metformin in kidney tissue [28].…”
Section: Introductionmentioning
confidence: 86%
“…It is noteworthy that different viral infections bring different changes of the renal transporter levels. The poly I:C infected pregnant rat showed lowered levels of OAT1/3, OATP4C1, BCRP, and MRP2 ( Karimian Pour and Piquette-Miller, 2020 ), but the HIV-1 transgenic rat showed reduced OCT2 and MATE1 levels ( Karimian Pour and Piquette-Miller, 2018 ). A hepatitis B virus infection could also damage kidneys, and it could downregulate some kidney transporters ( Zuo et al, 2020 ).…”
Section: Effect Of Diseases On Transporter Expression and Functionmentioning
confidence: 99%